INCLUSIVE EDUCATION IN PRIMARY SCHOOLS: EVIDENCE-BASED STRATEGIES FOR SUPPORTING LEARNERS WITH SPECIAL EDUCATIONAL NEEDS - Jamil Khan; Razia Khan; Khalil Zaman; Dewi Ismu Purwaningsih (Yayasan Adra Karima Hubbi, 2026)
Inclusive education in primary schools has become a central priority in global education agendas, emphasizing the right of learners with special educational needs to access quality education within mainstream classrooms. Despite strong policy commitments, effective classroom-level implementation remains uneven, highlighting the need for evidence-based strategies that translate inclusion principles into practice. This study aims to identify and examine evidence-based instructional and organizational strategies that effectively support learners with special educational needs in inclusive primary school settings. The study employed a mixed-methods design combining systematic evidence review, classroom observations, semi-structured interviews, and analysis of school documents across multiple inclusive primary schools. Quantitative descriptive and inferential analyses were integrated with qualitative thematic analysis to examine strategy implementation and learner outcomes. The findings indicate that differentiated instruction, individualized support services, and collaborative teaching practices significantly enhance learner participation, engagement, and classroom inclusion. Inferential analysis demonstrates that higher levels of strategy implementation are associated with stronger learner engagement, while qualitative findings reveal improved peer interaction, confidence, and instructional responsiveness. The study concludes that inclusive education is most effective when evidence-based strategies are implemented coherently and systematically. Sustainable inclusion in primary schools requires alignment between empirical evidence, instructional practice, and institutional support to ensure equitable learning opportunities for learners with special educational needs.